Saudi Arabia : 2016 Article IV Consultation-Press Release; Staff Report; and Informational Annex. (IMF Staff Country Reports; Country Report ;, 2016)
Saudi Arabia has begun a fundamental policy shift to respond to low oil prices. The government has introduced a series of reforms over the past year and has recently set out plans for a bold and ambitious transformation of the Saudi Arabian economy in Vision 2030 and the National Transformation Program. Diversifying the economy, creating jobs for nationals in the private sector, and implementing a gradual, but sizable and sustained fiscal consolidation are key policy priorities.